The price of peace : incentives and international conflict prevention - Cortright, David ((Carnegie Commission on Preventing Deadly Conflict Series))
Contenido: Panorama. Prevención de proliferación de armas. Resolución de conflictos regionales. Applicación multilateral. Conclusiones y lecciones.